THE ROLE OF GREEN INNOVATION IN MEDIATING THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE IN A CORPORATE LIFE CYCLE PERSPECTIVE - Estuti, Eni Puji; Natoil, Natoil (JURNAL STIE SEMARANG, 2024)
Issues regarding the environment are one of the important topics in global economic discussions today. The high expectations of the public about the need for companies to become more environmentally responsible. There are many ways that a company can do for the welfare of the surrounding community. Corporate Social Responsibility has been proven to influence green innovation. Green Innovation has a significant positive effect on firm value. Companies that disclose and issue CSR expenses in the current period will increase the company's value in the future. Green Innovation increases company value. CSR and GI have more impact on increasing the value of the company in the growth stage.